The impact of Brexit on the UK pharmaceutical supply chain: scoping review protocol - Milne-Ives, M; Lam, C; van Velthoven, M; Meinert, E (JMIR Publications, 2020)
Background: The continuing uncertainty around Brexit has caused concern in the pharmaceutical industry and among health care professionals and patients. The exact consequences of Brexit on the pharmaceutical supply chain in the United Kingdom will depend on whether a deal is reached and what it entails, but it is likely to be affected by the withdrawal of the United Kingdom from the European Union. Regulatory issues and delays in supply have the potential to negatively affect the ability of UK residents to receive an adequate and timely supply of necessary medicines.